The Effect of Gross Regional Domestic Product (GRDP) and Labor Force Participation Rate (TPAK) on the Welfare of the Community of East Kutai Regency With Income Level As A Mediator - Ita Ika Luciana; Aji Sofyan Effendi; Muhammad Awaluddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the influence of GRDP (Gross Regional Domestic Product) and Labor Force Participation Rate (LFPR) on the welfare of the people in East Kutai Regency, with income level as a mediating variable. The identified variables in this research include the level of community welfare, proxied by the Human Development Index (HDI) (Y2) as the dependent variable, while GRDP (X1) and Labor Force Participation Rate (LFPR) (X2) are independent variables, and income level (Y1) serves as a mediating variable. This study utilizes panel data from 2012 to 2022, using Partial Least Square (PLS) analysis.